A Study of Bird's Nest Tax Non-Compliance in Kutai Kartanegara Regency: An Attribution Theory Perspective: Studi Ketidakpatuhan Pajak Sarang Burung Walet di Kabupaten Kutai Kartanegara: Perspektif Teori Atribusi - Faudia Nur Bahtiar; Agus Setiawaty (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2026)
This study aims to uncover the factors causing non-compliance in the swallow's nest tax in Kutai Kartanegara from the perspective of the tax authorities and taxpayers. Qualitative approach used in this study with data collection was conducted through in-depth interviews with informants who are tax officials and taxpayers of swallow's nest. The results revealed that taxpayer non-compliance is caused by a lack of knowledge and awareness, ineffective socialization, uncertain income, high tax rates, minimal audits and application of tax sanctions, and the absence of an authority that regulates the market price of swallow's nest. This study recommends increasing tax socialization and sanction enforcement to improve taxpayer compliance. This study contributes to the development of tax implementation to focus on factors that can reduce non-compliance with the swallow's nest tax, thereby increasing regional revenue.